Fluoropolymer Coated DNA Nanoclews for Volumetric Visualization of Oligonucleotides Delivery and Near Infrared Light Activated Anti‐Angiogenic Oncotherapy - Peng Zhang; Ranran Guo; Haiting Zhang; Wuli Yang; Ye Tian (Advanced Science, 2023)
Abstract The potential of microRNA regulation in oncotherapy is limited by the lack of delivery vehicles. Herein, it is shown that fluoropolymer coated DNA nanoclews (FNCs) provide outstanding ability to deliver oligonucleotide through circulation and realize near infrared (NIR) light activated angiogenesis suppression to abrogate tumors. Oligonucleotides are loaded in DNA nanoclews through sequence specific bindings and then a fluorinated zwitterionic polymer is coated onto the surface of nanoclews. Further incorporating quantum dots in the polymer coating endows the vectors with NIR‐IIb (1500–1700 nm) fluorescence and NIR light triggered release ability. The FNC vector can deliver oligonucleotides to cancer cells systemically and realize on‐demand cytosolic release of the cargo with high transfection efficiency. Taking advantage of the NIR‐IIb emission, the whole delivery process of FNCs is visualized volumetrically in vivo with a NIR light sheet microscope. Loaded by FNCs, an oligonucleotide can effectively silence the target miRNA when activated with NIR light, and inhibit angiogenesis inside tumor, leading to complete ablation of cancer. These findings suggest FNCs can be used as an efficient oligonucleotide delivery platform to modulate the expression of endogenous microRNA in gene therapy of cancer.